INVESTIGATION OF CERAMIC ROOF, METALLIC ROOF AND CONCRETE ROOF THERMAL PERFORMANCE IN TROPICAL CLIMATE (Nalars, 2014)
ABSTRACT. The objectives of this research are to investigate thermal performance of ceramic roof, metallic roof, and concrete roof. Experimental buildings were located in Universiti Teknology PETRONAS (UTP), Perak, Malaysia that had three different types of roof: ceramic roof, metallic roof, and concrete roof. This research measured temperature outdoor and indoor. The results of this research were the highest outdoor and indoor temperature compared between three types of roofs was on metallic roof. The highest heat flux compared between three types of roofs was on metallic roof. The highest value of cooling energy compared between three types of roofs was on metallic roof. The room in building with metallic roof needs more energy to reduce temperature than room in building with ceramic roof and concrete roof.Â ABSTRAK. Tujuan dari penelitian ini adalah meneliti tentang suhu termal yang dihasilkan oleh atap genteng keramik, atap jenis logam, dan atap beton. Obyek untuk eksperimen dalam penelitian ini mengambil tiga bangunan dengan konstruksi atap berbeda (genteng keramik, logam, dan beton) yang berlokasi di Universiti Teknology PETRONAS. Penelitian ini menggunakan metode eksperimen dengan melakukan pengukuran suhu luar dan suhu dalam ruangan. Hasil penelitian ini menemukan bahwa atap jenis logam mempunyai suhu luar dan suhu dalam tertinggi, nilai heat flux tertinggi dibandingkan jenis atap genteng keramik dan atap beton, sehingga ruang dalam bangunan dengan jenis atap logam membutuhkan lebih banyak energi untuk menurunkan suhu ruangan dalam bangunan dibandingkan dengan atap jenis genteng keramik dan atap beton.